ORIENTASI TAFSIR, KOLONIALISME, DAN KEBANGSAAN (STUDI KONSTRUKSI TAFSIR VERBAL TUAN GURU ZAINUDDIN TERHADAP QS. AL-MAIDAH 44-45 DI UNIVERSITAS PTIQ JAKARTA - Darwis Hude; Zulkarnaen Zulkarnaen; Lukman Hakim; Ahmad Thib Raya; Imam Mutaqien; Irpan Husaini (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This study aims to analyze the verbal exegesis of Tuan Guru Zainuddin Abdul Madjid (1908-1997) on QS. Al-Maidah/5: 44-45. Tuan Guru was a traditional Islamic scholar born out of the Madrasah Shaulatiyyah in Mecca. This research is important for two reasons: first, it provides insights into how the Quran, exegesis, and the context during the colonial period are intertwined; second, it explains how exegesis serves as a historical document of the Lombok community where Tuan Guru lived. The hypothesis is that Tuan Guru’s verbal exegesis is a contextual interpretation emerging from the context of the struggle to maintain Indonesia's independence in 1946. Consequently, he refers to the term